Subcellular clustering of a putative c‐di‐GMP‐dependent exopolysaccharide machinery affecting macro colony architecture in Bacillus subtilis. Issue 3 (3rd February 2017) - Bedrunka, Patricia; Graumann, Peter L.
Summary: The structure of bacterial biofilms is predominantly established through the secretion of extracellular polymeric substances (EPS). They show that Bacillus subtilis contains an operon ( ydaJ ‐ N ) whose induction leads to increased Congo Red staining of biofilms and strongly altered biofilm architecture, suggesting that it mediates the production of an unknown exopolysaccharide. Supporting this idea, overproduction of YdaJKLMN leads to cell clumping during exponential growth in liquid culture, and also causes colony morphology alterations in wild type cells, as well as in a mutant background lacking the major exopolysaccharide of B . subtilis . The first gene product of the operon, YdaJ, appears to modify the overproduction effects, but is not essential for cell clumping or altered colony morphology, while the presence of the c‐di‐GMP receptor YdaK is required, suggesting an involvement of second messenger c‐di‐GMP. YdaM, YdaN and YdaK colocalize to clusters predominantly at the cell poles and are statically positioned at this subcellular site, similar to other exopolysaccharide machinery components in other bacteria. Their analysis reveals that B. subtilis contains a static subcellular assembly of an EPS machinery that affects cell aggregation and biofilm formation.